Application of the Pick Function in the Lieb Concavity Theorem for Deformed Exponentials - Yang, Guozeng; Li, Yonggang; Wang, Jing; Sun, Huafei (Fractal and fractional, 2022)
The Lieb concavity theorem, successfully solved in the Wigner–Yanase–Dyson conjecture, is an important application of matrix concave functions. Recently, the Thompson–Golden theorem, a corollary of the Lieb concavity theorem, was extended to deformed exponentials. Hence, it is worthwhile to study the Lieb concavity theorem for deformed exponentials. In this paper, the Pick function is used to obtain a generalization of the Lieb concavity theorem for deformed exponentials, and some corollaries associated with exterior algebra are obtained.